2022
DOI: 10.3390/molecules27134239
|View full text |Cite
|
Sign up to set email alerts
|

The Health-Promoting and Sensory Properties of Tropical Fruit Sorbets with Inulin

Abstract: Inulin is a popular prebiotic that is often used in the production of ice cream, mainly to improve its consistency. It also reduces the hardness of ice cream, as well as improving the ice cream’s organoleptic characteristics. Inulin can also improve the texture of sorbets, which are gaining popularity as an alternative to milk-based ice cream. Sorbets can be an excellent source of natural vitamins and antioxidants. The aim of this study was to evaluate the effect of the addition of inulin on the sensory charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…After 60 min, the volume of leakage was read from the cylinder. The test was carried out at a temperature of 20 • C [42].…”
Section: Physico-chemical Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…After 60 min, the volume of leakage was read from the cylinder. The test was carried out at a temperature of 20 • C [42].…”
Section: Physico-chemical Parametersmentioning
confidence: 99%
“…A defined volume of the sample (cut from the product with a cylinder) was transferred to a volumetric flask and made up to the mark with distilled water. Based on the known volume of the volumetric flask, the volume of the cylinder, and the amount of added water, the overrun of the sorbets was calculated [42].…”
Section: Physico-chemical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent article showed that amaranth proteins could be embedded within the matrix of lemon sorbet as a potential functional protein source to increase bioactive peptides and antithrombotic activity [31]. Likewise, avocado, kiwi, honey melon, yellow melon and mango sorbets have also been studied with the embedded prebiotic inulin, which ultimately increased the organoleptic and pro-health features of the sorbets [37].…”
Section: Sorbet As a Potential Functional Foodmentioning
confidence: 99%
“…In the freezer, the mix turns into a viscous foam due to the penetration and redistribution of air in the volume of the product. At the same time, free water present in the mix freezes with the formation of ice crystals, which form an exceptional and desirable texture of ice cream [ 2 , 3 ]. In the case of the formation of large ice crystals, the sensory properties of ice cream deteriorate significantly [ 4 ], which requires control of the process of crystallization of free water during production and storage of the finished product.…”
Section: Introductionmentioning
confidence: 99%